2022
DOI: 10.1200/go.21.00163
|View full text |Cite
|
Sign up to set email alerts
|

HIV and Hodgkin Lymphoma Survival: A Prospective Study in Botswana

Abstract: PURPOSE People living with HIV (PLWH) experience increased risk of Hodgkin lymphoma (HL) despite effective initiation of antiretroviral therapy (ART). In high-income countries, outcomes following HIV HL have been reported to be non-differential, or inferior for PLWH. We sought to assess the effect of HIV on HL survival in Botswana, an African country with a generalized HIV epidemic and high ART coverage, to describe a context more reflective of global HIV populations. PATIENTS AND METHODS In the Thabatse Cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
1
11
1
Order By: Relevance
“…HIV-associated lymphoma (HAL) is a common malignancy in South Africa (Wang, Jun & Yao, 2022 ), although there are limited data from South Africa on HL (Rapiti et al 2022 ). This study found HIV a comorbid disease in most patients treated for lymphomas which is in line with published literature (Moahi et al 2022 ).…”
Section: Discussion Of Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…HIV-associated lymphoma (HAL) is a common malignancy in South Africa (Wang, Jun & Yao, 2022 ), although there are limited data from South Africa on HL (Rapiti et al 2022 ). This study found HIV a comorbid disease in most patients treated for lymphomas which is in line with published literature (Moahi et al 2022 ).…”
Section: Discussion Of Resultssupporting
confidence: 92%
“…With the introduction of highly active antiretroviral therapy (HAART) and the expected improved life expectancy, malignancies have become the leading cause of disease and death in people with HIV. Although HL is not considered an AIDS-defining disease, the incidence of HL in HIV-infected individuals is higher compared to the general population (Moahi et al 2022 ). More than 28% of HIV-related deaths are ascribed to malignant tumours and AIDS-associated lymphomas are found in more than 40% of HIV-infected individuals (Berhan, Bayleyegn & Getaneh 2022 ).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…However, other studies do not confirm any significant difference between the mortality of HIV-infected and non-infected HL patients. [ 5 , 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies do not confirm any significant difference between the mortality of HIV-infected and non-infected HL patients. [5,27] According to Olszewski et al, [26] the frequency of relapses among HL seropositive patients is associated with a T CD4 + count below 200, indicating severe immunodeficiency. Furthermore, Castillo et al [9] conclude that a T CD4 + count < 200 was an independent adverse prognostic factor for disease-free survival and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Good results have also been reported with BEACOP (bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, procarbazine, prednisolone) with a complete response rate of 86% and 2-year overall survival of 91% in PLWH with advanced Hodgkin lymphoma. However, BEA-COPP is rarely used in frontline therapy because of its high toxicity (dose reduction/delay > 50%, TMR 6%) [6,32].…”
Section: Hodgkin Lymphomamentioning
confidence: 99%